Stimulating Effect of Hydrogen on N2 Fixation in Association with Field-Grown Wetland Rice - Gowda, T. K. S.; Watanabe, I. (Canadian Science Publishing, 1985)
The addition of H2 (10% by volume) stimulated acetylene reduction associated with excised roots, decapitated plants, and intact plants of rice grown in a continuously flooded field. Excised roots showed H2-uptake activitiy. Stimulation of N2 fixation by H2 in association with field-grown decapitated rice plants was confirmed by 15N2 incorporation.